Philadelphia chromosome-positive mixed-phenotype acute leukemia: a case report and literature review - Yang, Liqing; Huang, Meijuan; Chen, Yuanzhong; Wu, Yong (Frontiers in Oncology, 2025)
IntroductionMixed-phenotype acute leukemia (MPAL) is a rare type of acute leukemia with an incidence of less than 5% and Philadelphia chromosome-positive (Ph+) represents a distinct subtype.Case descriptionAn 18-year-old female complained of recurrent fever with fatigue and chills for one month, and a week of growing lymphadenectasis. Bone marrow examination revealed two distinct populations of blast cells and the presence of BCR::ABL1 fusion gene, leading to a diagnosis of Ph+ MPAL. The patient received induction chemotherapy of DVAP regimen combined with tyrosine kinase inhibitors (TKIs), and underwent allogeneic hematopoietic stem cell transplantation after achieving complete remission. To date, the patient has maintained sustained hematological and molecular complete remission.ConclusionA literature review of 59 cases revealed that Ph+ MPAL is more common in adult, male patients and primarily manifests as B/myeloid subtype. Higher leukocyte counts and chromosome -7 abnormalities have been identified as poor prognostic markers. Acute lymphoblastic leukemia-type therapy is considered more effective for patients with MPAL, and in the TKI era Ph+ has become a subtype with a better prognosis.